Inhibition Mechanism of PinX1 Gene on Cancer Stem Cells of Nasopharyngeal Carcinoma: Effects of PinX1 Gene on Cancer Stem Cells - Xiang, Hua; Liu, Linghui; Yuan, Yuzhu; Liu, Longqing; Chen, Zhiwei (Cellular and Molecular Biology, 2022)
The recurrence and long-term metastasis of these tumors are important causes of treatment failure and death. On the other hand, PinX1 is a nucleolar protein found in recent years that can interact with telomere/telomerase simultaneously, and it is highly conserved in human and yeast. Some studies have shown that the PinX1 gene can inhibit the tumor stem cells of NPC. Therefore, the mechanism of inhibition of the PinX1 gene on the tumor stem cells of NPC has been studied in this paper. In this paper, CNE2 cells of NPC were used as experimental materials, CD133 as a marker, PinX1 overexpression plasmids and their corresponding empty plasmids were respectively transfected in CD133+ cells, PinX1 siRNA and their corresponding NC siRNA were respectively transfected in CD133- cells for control experiments. In this study, we found that the telomerase activity of the CD133 - + NC group was 1.001 ± 0.086, the CD133 - + pinx1sirna group was 0.974 ± 0.046, CD133+ + vector group was 0.928 ± 0.102, CD133+ + over PinX1 group was 0.703 ± 0.086. Therefore, the PinX1 gene can inhibit NPC stem cells by inhibiting telomerase activity.